(untitled) (Lex localis - Journal of Local Self-Government, 2025)
In the last ten years, India’s Fintech industry has grown exponentially, delivering revolutionary changes in the face of financial services. Driven by advances in technology, regulatory backing, expanding digital consumer universe, and rising smartphone and internet penetration, Fintech has not only transformed traditional bank models but also enabled financial inclusion, economic empowerment, and employment generation. This research investigates the multi-faceted effect of Fintech on India’s economy, specifically in terms of digital payments, blockchain technology usage, alternative payment systems, and investment and banking services. Based on a systematic review of literature, this paper critically discusses the way technology such as UPI, Aadhaar-based services, and digital platforms have made financial inclusion possible, lowered operating costs, and democratized access to financial products for the underprivileged. The research also identifies regulatory issues, cybersecurity threats, and institutional response to such disruption, calling for robust regulatory mechanisms to protect consumers as well as financial institutions. The research also evaluates Fintech’s contribution toward credit accessibility for MSMEs and its macroeconomic impact in general. This report seeks to give insights into the future direction of Fintech in India and provide policy suggestions for a secure and inclusive digital financial environment.